Blocks identical by descent in the genomes of the indigenous population of Siberia demonstrate genetic links between populations - N. A. Kolesnikov; V. N. Kharkov; K. V. Vagaitseva; A. A. Zarubin; V. A. Stepanov (Вавиловский журнал генетики и селекции)
The gene pool of the indigenous population of Siberia is a unique system for studying population and evolutionary genetic processes, analyzing genetic diversity, and reconstructing the genetic history of populations. High ethnic diversity is a feature of Siberia, as one of the regions of the peripheral settlement of modern human. The vast expanses of this region and the small number of aboriginal populations contributed to the formation of significant territorial and genetic subdivision. About 40 indigenous peoples are settled on the territory of the Siberian historical and ethnographic province. Within the framework of this work, a large-scale population study of the gene pool of the indigenous peoples of Siberia was carried out for the first time at the level of high-density biochips. This makes it possible to fill in a significant gap in the genogeographic picture of the Eurasian population. For this, DNA fragments were analyzed, which had been inherited without recombination by each pair of individuals from their recent common ancestor, that is, segments (blocks) identical by descent (IBD). The distribution of IBD blocks in the populations of Siberia is in good agreement with the geographical proximity of the populations and their linguistic affiliation. Among the Siberian populations, the Chukchi, Koryaks, and Nivkhs form a separate cluster from the main Siberian group, with the Chukchi and Koryaks being more closely related. Separate subclusters of Evenks and Yakuts, Kets and Chulyms are formed within the Siberian cluster. Analysis of SNPs that fell into more IBD segments of the analyzed populations made it possible to compile a list of 5358 genes. According to the calculation results, biological processes enriched with these genes are associated with the detection of a chemical stimulus involved in the sensory perception of smell. Enriched for the genes found, molecular pathways are associated with the metabolism of linoleic, arachidonic, tyrosic acids and by olfactory transduction. At the same time, an analysis of the literature data showed that some of the selected genes, which were found in a larger number of IBD blocks in several populations at once, can play a role in genetic adaptation to environmental factors.